Evaluation of the crystallization process of Stevia rebaudiana Bertoni - Matheus, Giulia; Picone, Carolina (Revista dos Trabalhos de Iniciação Científica da UNICAMP, 2019)
Nowadays, the search for foods with reduced sugars, fats and calories has grown. Many studies in the area have gained space, among them the substitution of sucrose in food for another natural sweetener. Stevia is a sweetener with potential to serve this growing segment. However, it has a lower solubility than sucrose, which could limit stevia industrial application. Despite of its technological relevance, few information is available about stevia crystallization and the factors that influence such process still unknown. The aim of this project was to understand the mechanisms of stevia crystallization and to identify the factors that influence such process. Three comercial samples with different concentrations of rebaudioside A were evaluated. Each sample was analized regarding their centesimal composition. Tests of absorbance, pH, XRD, optical microscopy and solubility were also carried out in different temperatures. The results showed that more concentrated solutions and elevated temperatures provide faster and more intense crystallization. Moreover, samples with a higher percentage of rebaudioside A have greater tendency to crystallize than those with low content of rebaudioside A, which did not crystallize in any of the situations. Therefore, it was possible to conclude that the stevia crystallization process is influenced both by the rebaudioside A content, as well as by the concentration of the solutions prepared and the temperature at which such solutions are storage.